Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12978-020-0885-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of primary and secondary sexual abstinence among never-married youth in urban poor Accra, Ghana

Abstract: Background: Sexual abstinence is a key component of the strategy to address unwanted pregnancies, sexually transmitted infections and HIV among youth in sub-Sahara Africa. But contextual pressures make abstaining from sex a formidable task for urban poor youth in the sub-region. Nevertheless, some youth in these settings still manage to resist the pressure to initiate sex early, while others choose abstinence after an initial sexual debut. Few studies in the sub-region have examined sexual abstinence among urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…Lastly, a considerable number (25%) of facilities indicated that they do not provide contraceptives to unmarried adolescents. Failure to provide contraceptives to adolescents worsens their vulnerabilities, a situation that is even worse among those living in informal settlements given their social-economic status ( 50 , 51 ). Because of their comparatively poorer social-economic status, unmarried adolescents living in informal settlements will be more prone to sexual assault and would engage in more risky sexual behavior ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, a considerable number (25%) of facilities indicated that they do not provide contraceptives to unmarried adolescents. Failure to provide contraceptives to adolescents worsens their vulnerabilities, a situation that is even worse among those living in informal settlements given their social-economic status ( 50 , 51 ). Because of their comparatively poorer social-economic status, unmarried adolescents living in informal settlements will be more prone to sexual assault and would engage in more risky sexual behavior ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sexual abstinence among adolescents is highly associated with good sexual communication between adolescents and their parents [42][43]. In our study, rural adolescents who had never had sexual intercourse had higher odds of discussing sexual matters with their parents relative to adolescents who had ever had sex.…”
Section: Discussionmentioning
confidence: 50%
“…The respondents were also asked about their participation in Adolescent health clubs which are common in the study district. The measurement of the predictor variables was guided by previous studies [36, [37][38][39][40][41][42][43] Data processing and analysis Both descriptive (frequency distribution tables) and inferential statistics (bivariate and multivariate analysis) was used in the analysis. The bivariate analysis examined the association between the outcome and predictor variables.…”
Section: Outcome and Predictor Variablesmentioning
confidence: 99%
“…Communication with friends, peer pressure and advertisements of media, etc. have a powerful impact on adolescents and growing children (Alhassan & Dodoo, 2020). The influence of parents in shaping social and moral values and the conventional school curriculum is becoming progressively unable of preparing children capable of the skills, which they needed to face practical life (Shek et al, 2020).…”
Section: The Need Of Life Skills Education In Schoolsmentioning
confidence: 99%
“…Life skills education influences some manifestations positively on the academic performance of children. As soon as the pupils or students start to feel that they are being involved in matters of relevance to their personal lives, they contribute more and study more (Alhassan & Dodoo, 2020;Parsons, Hunter, & Warne, 1988). iii.…”
Section: Imentioning
confidence: 99%